German climate legislation on the pathway to the 1.5°C Temperature goal? - Stäsche, Uta (Christ University Law Journal, 2022)
Climate lawsuits are rising worldwide. Correspondingly, there are a growing number of landmark rulings by courts. On 29 April 2021, the German Federal Constitutional Court (BVerfG), issued its significant Order on the deficiencies of German Climate Change legislation. This paper analyses in detail the court’s key deliberations and outlines its unacceptable features. In this context, the similarities and differences between the Court Order and the historic Urgenda ruling of the Hoge Raad, the Supreme Court of the Netherlands, are illustrated. This paper explores the reasons why the amended German Climate Change Act of 2021, also lacks compatibility with the Basic Law of Germany, i.e., its Constitution. In the last section, the serious consequences of the current European security crisis caused by Russia’s war against Ukraine are highlighted. Here, the strong interweaving of fossil energy dependence and climate emergency is shown.